2022
DOI: 10.21926/obm.icm.2201013
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of Zingiber officinale Extract and Sodium Valproate Ameliorates Seizure Severity, Cognitive Deficit, and Neuronal Cell Loss in Pentylenetetrazole-kindled Mice

Abstract: Preparations of Zingiber officinale are used in Nigerian folk medicine to manage colds, pain, arthritis, nausea, and epilepsy. The ameliorative effects of co-administering aqueous Zingiber officinale extract (GE) and sodium valproate (SDV) on pentylenetetrazole-kindled mice were evaluated regarding cognitive deficits, neuronal cell loss, and seizure severity. GFAP was also quantified. Male mice were pretreated with GE (50 mg/kg), SDV (100 and 200 mg/kg), and GE + SDV before kindling. After kindling, the mice u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Rhizome of ginger (Zingiber officinale Roscoe, Zingiberaceae) has been used as spice, flavouring agent and in many traditional medicines for its health-promoting properties. Previous studies reported that aqueous and ethanol extracts of ginger have anticonvulsant effect (Hosseini and Mirazi, 2015;Hosseini et al, 2016;Yakubu et al, 2019). The present study aimed at comparing the anticonvulsant effect of ethanol (polar solvent) and ethylacetate (nonpolar solvent) extracts of Zingiber officinale (ginger).…”
Section: Introductionmentioning
confidence: 93%
“…Rhizome of ginger (Zingiber officinale Roscoe, Zingiberaceae) has been used as spice, flavouring agent and in many traditional medicines for its health-promoting properties. Previous studies reported that aqueous and ethanol extracts of ginger have anticonvulsant effect (Hosseini and Mirazi, 2015;Hosseini et al, 2016;Yakubu et al, 2019). The present study aimed at comparing the anticonvulsant effect of ethanol (polar solvent) and ethylacetate (nonpolar solvent) extracts of Zingiber officinale (ginger).…”
Section: Introductionmentioning
confidence: 93%